Rabbit meat burgers with pitahaya peel powder: Functional, physicochemical and sensory analysis - Benavides-Gonzalez, Marcia; Zambrano-Zambrano, Rocío; García-Mendoza, Jordan; Avellán-Avellán, Lila; Muñoz-Murillo, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Nowadays, it is necessary to seek alternative agroindustrial uses of fruit residues, as these are sources of bioactive compounds important for human nutrition. The objective of this study was to evaluate the effect of pitahaya peel powder on the functional, physicochemical, and sensory acceptability properties of rabbit meat burgers. Five formulations of rabbit burger meat with pitahaya peel powder (3, 5, 7, and 9 %) and a control formulation were established under a completely randomized experimental design with a factorial arrangement. In the processed products, functional properties (anthocyanin content, antioxidant activity (DPPH and ABTS) and total phenols), physicochemical properties (pigmentation of the ether extract, protein, fat, fiber, ash, moisture and total solids), textural and colorimetric characteristics (hardness, cohesiveness, adhesiveness, gumminess and color), microbiological properties (mesophilic aerobes, Escherichia coli, Staphylococcus aureus and Salmonella) and sensory attributes (flavor, aroma, color and texture) were determined. The treatment with the best physicochemical and functional properties was T4 (9 % ppp) whose values were: fat (2.48 %); fiber (3.86 %); a* (23.06); b* (3.47), anthocyanins (+++), DPPH (23.667 µmol trolox equivalent.g-1), ABTS (30.353 µmol trolox equivalent.g-1), total phenols (19.706 mg gallic acid equivalent.g-1); pigmentation (0.113), hardness (4.552 N), adhesiveness (-0.855 N) and gumminess (2.128 N). All treatments met the physicochemical and microbiological requirements established in the Ecuadorian standard NTE INEN 1338.